An Exploratory Study Using Next-Generation Sequencing to Identify Prothrombotic Variants in Patients with Cerebral Vein Thrombosis. - Kramer, Robert Anton; Zimmermann, Robert; Strobel, Julian; Achenbach, Susanne; Stroebel, Armin; Hackstein, Holger; Messerer, David Alexander Christian; Schneider, Sabine (International Journal of Molecular Sciences, 2023)
Prothrombotic hereditary risk factors for cerebral vein thrombosis (CVT) are of clinical interest to better understand the underlying pathophysiology and stratify patients for the risk of recurrence. This study explores prothrombotic risk factors in CVT patients. An initial screening in patients of the outpatient clinic of the Department of Transfusion Medicine and Hemostaseology of the University Hospital Erlangen, Germany, revealed 183 patients with a history of CVT. An initial screening identified a number of common prothrombic risk factors, including Factor V Leiden (rs6025) and Prothrombin G20210A (rs1799963). All patients without relevant findings (58 individuals) were invited to participate in a subsequent genetic analysis of 55 relevant genes using next-generation sequencing (NGS). Three intron variants (ADAMTS13: rs28446901, FN1: rs56380797, rs35343655) were identified to occur with a significantly higher frequency in the CVT patient cohort compared to the general European population. Furthermore, the combined prevalence of at least two of four potentially prothrombic variants (FGA (rs6050), F13A1 (rs5985), ITGB3 (rs5918), and PROCR (rs867186)) was significantly higher in the CVT subjects. The possible impact of the identified variants on CVT is discussed.
EVALuna2:535884

Arabidopsis INOSITOL TRANSPORTER2 mediates H+ symport of different inositol epimers and derivatives across the plasma membrane. - Schneider, Sabine; Schneidereit, Alexander; Udvardi, Patrick; Hammes, Ulrich; Gramann, Monika; Dietrich, Petra; Sauer, Norbert (Plant Physiology, 2007)
Of the four genes of the Arabidopsis (Arabidopsis thaliana) INOSITOL TRANSPORTER family (AtINT family) so far only AtINT4 has been described. Here we present the characterization of AtINT2 and AtINT3. cDNA sequencing revealed that the AtINT3 gene is incorrectly spliced and encodes a truncated protein of only 182 amino acids with four transmembrane helices. In contrast, AtINT2 codes for a functional transporter. AtINT2 localization in the plasma membrane was demonstrated by transient expression of an AtINT2-GREEN FLUORESCENT PROTEIN fusion in Arabidopsis and tobacco (Nicotiana tabacum) epidermis cells and in Arabidopsis protoplasts. Its functional and kinetic properties were determined by expression in yeast (Saccharomyces cerevisiae) cells and Xenopus laevis oocytes. Expression of AtINT2 in a Deltaitr1 (inositol uptake)/Deltaino1 (inositol biosynthesis) double mutant of bakers' yeast complemented the deficiency of this mutant to grow on low concentrations of myoinositol. In oocytes, AtINT2 mediated the symport of H(+) and several inositol epimers, such as myoinositol, scylloinositol, d-chiroinositol, and mucoinositol. The preference for individual epimers differed from that found for AtINT4. Moreover, AtINT2 has a lower affinity for myoinositol (K(m) = 0.7-1.0 mm) than AtINT4 (K(m) = 0.24 mm), and the K(m) is slightly voltage dependent, which was not observed for AtINT4. Organ and tissue specificity of AtINT2 expression was analyzed in AtINT2 promoter/reporter gene plants and showed weak expression in the anther tapetum, the vasculature, and the leaf mesophyll. A T-DNA insertion line (Atint2.1) and an Atint2.1/Atint4.2 double mutant were analyzed under different growth conditions. The physiological roles of AtINT2 are discussed.

Arabidopsis INOSITOL TRANSPORTER4 mediates high-affinity H+ symport of myoinositol across the plasma membrane. - Schneider, Sabine; Schneidereit, Alexander; Gramann, Monika; Sauer, Norbert; et al. (Plant Physiology, 2006)
Four genes of the Arabidopsis (Arabidopsis thaliana) monosaccharide transporter-like superfamily share significant homology with transporter genes previously identified in the common ice plant (Mesembryanthemum crystallinum), a model system for studies on salt tolerance of higher plants. These ice plant transporters had been discussed as tonoplast proteins catalyzing the inositol-dependent efflux of Na(+) ions from vacuoles. The subcellular localization and the physiological role of the homologous proteins in the glycophyte Arabidopsis were unclear. Here we describe Arabidopsis INOSITOL TRANSPORTER4 (AtINT4), the first member of this subgroup of Arabidopsis monosaccharide transporter-like transporters. Functional analyses of the protein in yeast (Saccharomyces cerevisiae) and Xenopus laevis oocytes characterize this protein as a highly specific H(+) symporter for myoinositol. These activities and analyses of the subcellular localization of an AtINT4 fusion protein in Arabidopsis and tobacco (Nicotiana tabacum) reveal that AtINT4 is located in the plasma membrane. AtINT4 promoter-reporter gene plants demonstrate that AtINT4 is strongly expressed in Arabidopsis pollen and phloem companion cells. The potential physiological role of AtINT4 is discussed.

Functional and physiological characterization of Arabidopsis INOSITOL TRANSPORTER1, a novel tonoplast-localized transporter for myo-inositol. - Schneider, Sabine; Beyhl, Diana; Hedrich, Rainer; Sauer, Norbert (The Plant Cell, 2008)
Arabidopsis thaliana INOSITOL TRANSPORTER1 (INT1) is a member of a small gene family with only three more genes (INT2 to INT4). INT2 and INT4 were shown to encode plasma membrane-localized transporters for different inositol epimers, and INT3 was characterized as a pseudogene. Here, we present the functional and physiological characterization of the INT1 protein, analyses of the tissue-specific expression of the INT1 gene, and analyses of phenotypic differences observed between wild-type plants and mutant lines carrying the int1.1 and int1.2 alleles. INT1 is a ubiquitously expressed gene, and Arabidopsis lines with T-DNA insertions in INT1 showed increased intracellular myo-inositol concentrations and reduced root growth. In Arabidopsis, tobacco (Nicotiana tabacum), and Saccharomyces cerevisiae, fusions of the green fluorescent protein to the C terminus of INT1 were targeted to the tonoplast membranes. Finally, patch-clamp analyses were performed on vacuoles from wild-type plants and from both int1 mutant lines to study the transport properties of INT1 at the tonoplast. In summary, the presented molecular, physiological, and functional studies demonstrate that INT1 is a tonoplast-localized H(+)/inositol symporter that mediates the efflux of inositol that is generated during the degradation of inositol-containing compounds in the vacuolar lumen.

Identification of an Arabidopsis solute carrier critical for intracellular transport and inter-organ allocation of molybdate - Gasber, A.; Klaumann, S.; Trentmann, O.; Trampczynska, A.; Clemens, Stephan; Schneider, Sabine; Sauer, Norbert; Feifer, I.; Bittner, F.; Mendel, R. R.; Neuhaus, H. E. (Plant Biology, 2011)
Plants represent an important source of molybdenum in the human diet. Recently, MOT1 has been identified as a transport protein responsible for molybdate import in Arabidopsis thaliana L.; however, the function of the homologous protein MOT2 has not been resolved. Interestingly, MOT2-GFP analysis indicated a vacuolar location of this carrier protein. By site directed mutagenesis at the N-terminal end of MOT2, we identified a di-leucine motif that is essential for driving the protein into the vacuolar membrane. Molybdate quantification in isolated vacuoles showed that this organelle serves as an important molybdate store in Arabidopsis cells. When grown on soil, leaves from mot2 T-DNA mutants contained more molybdate, whereas mot2 seeds contained significantly less molybdate than corresponding wild-type (Wt) tissues. Remarkably, MOT2 mRNA accumulates in senescing leaves and mot2 leaves from plants that had finished their life cycle had 15-fold higher molybdate levels than Wt leaves. Reintroduction of the endogenous MOT2 gene led to a Wt molybdate phenotype. Thus, mot2 mutants exhibit impaired inter-organ molybdate allocation. As total concentrations of the molybdenum cofactor (Moco) and its precursor MPT correlates with leaf molybdate levels, we present novel evidence for an adjustment of Moco biosynthesis in response to cellular MoO levels. We conclude that MOT2 is important for vacuolar molybdate export, an N-terminal di-leucine motif is critical for correct subcellular localisation of MOT2 and activity of this carrier is required for accumulation of molybdate in Arabidopsis seeds. MOT2 is a novel element in inter-organ translocation of an essential metal ion. © 2011 German Botanical Society and The Royal Botanical Society of the Netherlands.
Keywords: Micronutrient; Molybdate; Solute carrier; Transport; Vacuole

Inositol transporters AtINT2 and AtINT4 regulate arsenic accumulation in Arabidopsis seeds - Duan, Gui-Lan; Hu, Ying; Schneider, Sabine; Mcdermott, Joseph; Chen, Jian; Sauer, Norbert; Rosen, Barry P.; Daus, Birgit; Liu, Zijuan; Zhu, Yong-Guan (Nature Plants, 2015)
Arsenic contamination of groundwater and soils threatens the health of tens of millions of people worldwide. Understanding the way in which arsenic is taken up by crops such as rice, which serve as a significant source of arsenic in the human diet, is therefore important. Membrane transport proteins that catalyse arsenic uptake by roots, and translocation through the xylem to shoots, have been characterized in a number of plants, including rice. The transporters responsible for loading arsenic from the xylem into the phloem and on into the seeds, however, are yet to be identified. Here, we show that transporters responsible for inositol uptake in the phloem in Arabidopsis also transport arsenic. Transformation of Saccharomyces cerevisiae with AtINT2 or AtINT4 led to increased arsenic accumulation and increased sensitivity to arsenite. Expression of AtINT2 in Xenopus laevis oocytes also induced arsenite import. Disruption of AtINT2 or AtINT4 in Arabidopsis thaliana led to a reduction in phloem, silique and seed arsenic concentrations in plants fed with arsenite through the roots, relative to wild-type plants. These plants also exhibited a large drop in silique and seed arsenic concentrations when fed with arsenite through the leaves. We conclude that in Arabidopsis, inositol transporters are responsible for arsenite loading into the phloem, the key source of arsenic in seeds.

Novel PSI domains in plant and animal H+-inositol symporters. - Dotzauer, Dorina; Wolfenstetter, Susanne; Eibert, Dorothee; Schneider, Sabine; Dietrich, Petra; Sauer, Norbert (Traffic (Copenhagen, Denmark), 2010)
Inositols are indispensable components of cellular signaling molecules, and impaired cytoplasmic inositol concentrations affect cellular development. Although most cells can synthesize inositol de novo, plasma membrane-localized inositol uptake systems are indispensable for normal development. Here, we present in-depth functional analyses of plasma membrane-localized H(+)-inositol symporters from human and from the higher plant Arabidopsis thaliana. Sequence comparisons, structural and phylogenetic analyses revealed that these transporters possess conserved extracellular loop domains that represent homologs of plexins/semaphorin/integrin (PSI) domains from animal type I receptors. In these receptors, PSI domains modulate intracellular signaling via extracellular protein-protein interactions. Comparisons of H(+)-inositol symporters with wild type, mutated and truncated PSI domains in different expression systems showed that removal of the entire loop domain increased the V(max) of inositol uptake. Finally, we show that the PSI domains are targets for Ni(++) ions that cause a complete loss of transport activity. A possible role of Ni(++)-binding to PSI domains in Ni(++)-induced carcinogenicity is discussed.

Protein S Erlangen: a novel PROS1 gene mutation associated with quantitative protein S deficiency - Schneider, Sabine; Reissig, Julian; Weisbach, Volker Günter; Achenbach, Susanne; Hackstein, Holger; Strobel, Julian (Blood Coagulation & Fibrinolysis, 2022)
The members of a Caucasian family were genetically analyzed on suspicion of hereditary protein S deficiency. A novel mutation, c.1904T>C, associated with severe quantitative protein S deficiency was found. The novel PROS1 mutation was identified by sequencing of the PROS1 gene coding sequence. The identified c.1904T>C point mutation results in p.Phe635Ser amino acid exchange, which is located in the Laminin G-like 2 domain of protein S. Computational analysis indicates that this amino acid exchange affects the correct folding of the protein S antigen. Furthermore, this mutation is located in a region of the Laminin G-like 2 domain where changes in the amino acid sequence often result in decreased secretion. We postulate that the novel p.Phe635Ser mutation might lead to an incorrect folding, and thus, to a strongly impaired secretion of this protein S variant. We named this novel variant protein.
CRIS-Team Scopus Importer:2022-06-10

Proton-driven sucrose symport and antiport are provided by the vacuolar transporters SUC4 and TMT1/2 - Schulz, Alexander; Beyhl, Diana; Marten, Irene; Wormit, Alexandra; Neuhaus, Ekkehard; Poschet, Gernot; Buettner, Michael; Schneider, Sabine; Sauer, Norbert; Hedrich, Rainer (Plant Journal, 2011)
The vacuolar membrane is involved in solute uptake into and release from the vacuole, which is the largest plant organelle. In addition to inorganic ions and metabolites, large quantities of protons and sugars are shuttled across this membrane. Current models suggest that the proton gradient across the membrane drives the accumulation and/or release of sugars. Recent studies have associated AtSUC4 with the vacuolar membrane. Some members of the SUC family are plasma membrane proton/sucrose symporters. In addition, the sugar transporters TMT1 and TMT2, which are localized to the vacuolar membrane, have been suggested to function in proton-driven glucose antiport. Here we used the patch-clamp technique to monitor carrier-mediated sucrose transport by AtSUC4 and AtTMTs in intact Arabidopsis thaliana mesophyll vacuoles. In the whole-vacuole configuration with wild-type material, cytosolic sucrose-induced proton currents were associated with a proton/sucrose antiport mechanism. To identify the related transporter on one hand, and to enable the recording of symporter-mediated currents on the other hand, we electrophysiologically characterized vacuolar proteins recognized by Arabidopsis mutants of partially impaired sugar compartmentation. To our surprise, the intrinsic sucrose/proton antiporter activity was greatly reduced when vacuoles were isolated from plants lacking the monosaccharide transporter AtTMT1/TMT2. Transient expression of AtSUC4 in this mutant background resulted in proton/sucrose symport activity. From these studies, we conclude that, in the natural environment within the Arabidopsis cell, AtSUC4 most likely catalyses proton-coupled sucrose export from the vacuole. However, TMT1/2 probably represents a proton-coupled antiporter capable of high-capacity loading of glucose and sucrose into the vacuole. © 2011 Blackwell Publishing Ltd.
Keywords: antiport; glucose/sucrose transport; SUC4; symport; TMT1/TMT2; vacuole

Routes to the tonoplast: the sorting of tonoplast transporters in Arabidopsis mesophyll protoplasts. - Wolfenstetter, Susanne; Wirsching, Petra; Dotzauer, Dorina; Schneider, Sabine; Sauer, Norbert (The Plant Cell, 2012)
Vacuoles perform a multitude of functions in plant cells, including the storage of amino acids and sugars. Tonoplast-localized transporters catalyze the import and release of these molecules. The mechanisms determining the targeting of these transporters to the tonoplast are largely unknown. Using the paralogous Arabidopsis thaliana inositol transporters INT1 (tonoplast) and INT4 (plasma membrane), we performed domain swapping and mutational analyses and identified a C-terminal di-leucine motif responsible for the sorting of higher plant INT1-type transporters to the tonoplast in Arabidopsis mesophyll protoplasts. We demonstrate that this motif can reroute other proteins, such as INT4, SUCROSE TRANSPORTER2 (SUC2), or SWEET1, to the tonoplast and that the position of the motif relative to the transmembrane helix is critical. Rerouted INT4 is functionally active in the tonoplast and complements the growth phenotype of an int1 mutant. In Arabidopsis plants defective in the β-subunit of the AP-3 adaptor complex, INT1 is correctly localized to the tonoplast, while sorting of the vacuolar sucrose transporter SUC4 is blocked in cis-Golgi stacks. Moreover, we demonstrate that both INT1 and SUC4 trafficking to the tonoplast is sensitive to brefeldin A. Our data show that plants possess at least two different Golgi-dependent targeting mechanisms for newly synthesized transporters to the tonoplast.

SERPINC1 c.1247dupC: a novel SERPINC1 gene mutation associated with familial thrombosis results in a secretion defect and quantitative antithrombin deficiency - Ruf, Maximilian; Cunningham, Sarah; Wandersee, Alexandra; Brox, Regine; Achenbach, Susanne; Strobel, Julian; Hackstein, Holger; Schneider, Sabine (Thrombosis Journal, 2024)
BACKGROUND: Antithrombin (AT) is an important anticoagulant in hemostasis. We describe here the characterization of a novel AT mutation associated with clinically relevant thrombosis. A pair of sisters with confirmed type I AT protein deficiency was genetically analyzed on suspicion of an inherited SERPINC1 mutation. A frameshift mutation, c.1247dupC, was identified and the effect of this mutation was examined on the cellular and molecular level. METHODS: Plasmids for the expression of wild-type (WT) and mutated SERPINC1 coding sequence (CDS) fused to green fluorescent protein (GFP) or hemagglutinin (HA) tag were transfected into HEK293T cells. Subcellular localization and secretion of the respective fusion proteins were analyzed by confocal laser scanning microscopy and Western blot. RESULTS: The c.1247dupC mutation results in a frameshift in the CDS of the SERPINC1 gene and a subsequently altered amino acid sequence (p.Ser417LysfsTer48). This alteration affects the C-terminus of the AT antigen and results in impaired secretion as confirmed by GFP- and HA-tagged mutant AT analyzed in HEK293T cells. CONCLUSION: The p.Ser417LysfsTer48 mutation leads to impaired secretion, thus resulting in a quantitative AT deficiency. This is in line with the type I AT deficiency observed in the patients.
EVALuna2:553194
Keywords: Hereditary antithrombin deficiency; Secretion defect; Frameshift mutation; Thrombosis

The Protein S Erlangen Mutation PROS1c.1904T>C (F635S) Suppresses Secretion. - Reißig, Julian; Cunningham, Sarah; Wandersee, Alexandra; Brox, Regine; Achenbach, Susanne; Strobel, Julian; Hackstein, Holger; Schneider, Sabine (Clinical Laboratory, 2024)
BACKGROUND: The recently identified PROS1 mutation Protein S Erlangen c.1904T>C, resulting in amino acid exchange F635S, is associated with severe quantitative protein S (PS) deficiency and clinical thrombosis. It was hypothesized that this deficiency is due to a secretion defect [1]. This report aims to further elucidate the potential secretion defect of PS Erlangen. METHODS: Coding sequences (CDS) of wild type (WT) PROS1 (encoding PS) and mutated PROS1c.1904T>C (encoding PSF635S) were cloned in front of the CDS of green fluorescent protein (GFP), and the respective plasmids were introduced into HEK293T cells. PROS1-GFP and PROS1c.1904T>C-GFP expressing HEK293T cell lines were analyzed by confocal laser scanning microscopy and western blot for cellular proteins and proteins secreted to the growth medium. RESULTS: Western blot analysis revealed a significantly reduced secretion of PSF635S compared to WT PS. This observation was confirmed by the detection of mutant PSF635S-GFP fusion exclusively in the endoplasmic reticulum (ER), while PS-GFP passed through the entire secretory pathway, as indicated by the localization within both the ER and Golgi apparatus. CONCLUSIONS: The Protein S Erlangen mutation results in type I PS deficiency caused by a secretion defect.
EVALuna2:562075
Keywords: point mutation; PROS1; secretion pathway; Protein S deficiency; secretion defect

Vacuoles release sucrose via tonoplast-localised SUC4-type transporters. - Schneider, Sabine; Hulpke, Sabine; Schulz, A.; Yaron, I.; Höll, Janine; Imlau, Astrid; Schmitt, Bianca; Batz, Stefanie; Wolf, S.; Hedrich, Rainer; Sauer, Norbert (Botanica Acta, 2012)
Arabidopsis thaliana has seven genes for functionally active sucrose transporters. Together with sucrose transporters from other dicot and monocot plants, these proteins form four separate phylogenetic groups. Group-IV includes the Arabidopsis protein SUC4 (synonym SUT4) and related proteins from monocots and dicots. These Group-IV sucrose transporters were reported to be either tonoplast- or plasma membrane-localised, and in heterologous expression systems were shown to act as sucrose/H(+) symporters. Here, we present comparative analyses of the subcellular localisation of the Arabidopsis SUC4 protein and of several other Group-IV sucrose transporters, studies on tissue specificity of the Arabidopsis SUC4 promoter, phenotypic characterisations of Atsuc4.1 mutants and AtSUC4 overexpressing (AtSUC4-OX) plants, and functional comparisons of Atsuc4.1 and AtSUC4-OX vacuoles. Our data show that SUC4-type sucrose transporters from different plant families (Brassicaceae, Cucurbitaceae and Solanaceae) localise exclusively to the tonoplast, demonstrating that vacuolar sucrose transport is a common theme of all SUC4-type proteins. AtSUC4 expression is confined to the stele of Arabidopsis roots, developing anthers and meristematic tissues in all aerial parts. Analyses of the carbohydrate content of WT and mutant seedlings revealed reduced sucrose content in AtSUC4-OX seedlings. This is in line with patch-clamp analyses of AtSUC4-OX vacuoles that characterise AtSUC4 as a sucrose/H(+) symporter directly in the tonoplast membrane.

Voice- and health-related quality of life in the elderly - Plank, Christian Georg; Schneider, Sabine; Eysholdt, Ulrich; Schützenberger, Anne; Rosanowski, Frank (Journal of Voice, 2011)
Objective: Restrictions of verbal communication and high prevalence of voice disorders in the elderly are suspected to influence the quality of life. For assessment, both voice-specific and unspecific methods are already established and fundamental components of clinical diagnostics, but the question of correlation between voice-related and general health-related quality of life is still open in this subpopulation. Methods: One hundred and seven socially active persons aged 65+ years were recruited and asked to complete Voice-Related Quality of Life (V-RQOL) and Short Form (SF)-36 questionnaires. Results: There was a mild correlation between V-RQOL score and both of the SF-36 subscores (rs = 0.28 for the physical subscore and rs = 0.27 for the mental subscore). Conclusion: As correlation of voice- and health-related quality of life in elderly persons is only mild, both voice-specific and unspecific assessment methods are required for clinical diagnostics. © 2011 The Voice Foundation.
CRIS-Team Scopus Importer:2022-09-20
Keywords: Elderly; Quality of life; Voice